Generalization of the issues with implementing inclusive education in Ukraine empirical findings from sociological research experience - Iryna Hrabovets; Liudmyla Kalashnikova; Liudmyla Chernous (Ukrainian Journal of Educational Studies and Information Technology, 2022)
The focus of the paper is on the ongoing issues with the inclusion approach in the educational system. The authors make an effort to study legal documents governing inclusive education, the accessibility of medical and educational facilities, and the willingness of the teaching profession to engage with students who have special educational requirements. the empirical foundation created by a variety of empirical data gathered through traditional document analysis, parent and teacher interviews, and other means. The examination of the research's findings enables us to draw the conclusion that informants are well aware of the challenges facing inclusive education in the present. They are linked to the majority of school buildings' lack of architectural accessibility, teachers' inadequate professional preparation, experience interacting with kids who have various types and degrees of diseases, and the society's inadequate level of readiness to understand the concept of integration.